IMPLEMENTASI KEBIJAKAN KELUARGA BERENCANA DI KABUPATEN MAJALENGKA - Mumu Mugni; A Yunus; Diding Bajuri (Universitas Majalengka, 2020)
The implementation of the family planning policy program launched by the Indonesian government is not only focused on women, but also on men. This study uses a phenomenological approach. This is because the main objective of this study is to understand deeply (verstehen) the phenomenon that is the target of the study, namely the relatively low coverage of male family planning participation. In interpreting this understanding, researchers will try to draw various generalizations or theories that can be used for the development of science itself or to be used as a basis for the benefit of theory application in people's lives. The research method used in this study is a qualitative method and the informant selection technique in this study uses the snow ball informant technique. The data analysis technique used is taxonomic analysis, which is a more detailed and in-depth form of analysis in discussing a theme or subject matter. The implementation of Family Planning Policy in Majalengka Regency has gone quite well, this is indicated by the issuance of regional regulations (PERDA). Number 14 of 2016 concerning the Formation and Composition of Regional Apparatus of Majalengka Regency (Regional Gazette of Majalengka Regency of 2016 Number 14) regarding the establishment of the Office for Empowerment of Women for Child Protection and Family Planning as a technical agency that handles the family planning sector in Majalengka Regency and as a response to the decentralization of field authority Family Planning from the central government to local governments